IMPACT OF MONETARY POLICY ON AGRICULTURAL DOMESTIC PRODUCT IN IRAQ FOR THE PERIOD (1990- 2014) - & Ahmed, Salim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research aims to investigate the impact of monetary policy on agricultural GDP through monetary indicators such as exchange rate, interest rate, money supply and inflation for the period (1990-2014). The relationship was estimated through the (VECM) error correction model using statistical beam. The long - run  equilibrium relationship between the variables of the model and the results of the estimation of the relationship in the short  run revealed that the agricultural GDP is affected by the variables of monetary policy has been found that both inflation and money supply has a positive and significant the effect means that the increase in money supply by 1%  will lead to an increase in output. The GDP by 0.25% and this is Identically by  the economic logic, in other words, the expansion of any activity needs more capital just the increasing in  the inflation rate by 1% will  lead  to an increase in agricultural GDP by 0.05%.This means that the high level of prices encourages investors and producers to expand production capacities and increase production, while the price of exchange and the price of interest has not proved significant each. In the long term, the most influential variables are the interest rate as a 1% drop in interest rates will lead to higher GDP Agricultural by 0.3%.The Inflation came after the interest rate in terms of impact and came with positive signal and this is opposed   to economic logic. The research concluded that inflation has a positive effect on agricultural production in the short and long run. Furthermore, increasing the money supply by expanding credit has a significant role that exceeds the rest of the variables. The research recommended adopting an expansionary monetary policy while taking into consideration the control of inflation with reducing it in the future and contributing to price stability. Including prices of agricultural products and inputs. In addition to incentive private banks to expand agricultural credit and take into account the monetary indicators and development in the making of agricultural policies.